A comparison of nanoscale measurements with the theoretical models of real and nominal contact areas. (November 2020) - Xu, Yang; Jackson, Robert L; Chen, Yan; Zhang, Anqi; Prorok, Barton C
In this study, an experimental method is proposed to measure the real area of contact between an alumina sphere and an Al surface based on the adhesive transfer of the Au film and the scanning electron microscope in the back-scattered mode. A thin film of Au is sputtered on the alumina sphere before the indentation with the Al surface. After indentation, the interfaces of the alumina sphere and Al surface are observed by the scanning electron microscope. The contact area can be identified based on both the distributions of the alumina and Au on the alumina sphere and Al surface, respectively. The measured contact area at different nominal pressures are compared to predictions made by several popular theoretical elastic-plastic rough surface contact models.